2012
DOI: 10.1007/s10815-012-9890-z
|View full text |Cite
|
Sign up to set email alerts
|

Starting and resulting testosterone levels after androgen supplementation determine at all ages in vitro fertilization (IVF) pregnancy rates in women with diminished ovarian reserve (DOR)

Abstract: Purpose To investigate whether androgen conversion rates after supplementation with dehydroepiandrosterone (DHEA) differ, and whether differences between patients with diminished ovarian reserve (DOR) are predictive of pregnancy chances in association with in vitro fertilization (IVF).Methods In a prospective cohort study we investigated 213 women with DOR, stratified for age (≤38 or >38 years) and ovarian FMR1 genotypes/sub-genotypes. All women were for at least 6 weeks supplemented with 75 mg of DHEA daily p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 30 publications
3
44
0
Order By: Relevance
“…Androgens can augment FSH receptor expression in granulosa cells and are thought to promote follicular growth and estrogen biosynthesis by amplifying the effects of FSH in rhesus monkeys [15]. Studies on murine models of conditional granulosa cell and oocyte-specific deletion of the androgen receptor found positive correlations between androgen receptor and FSH receptor expression, suggesting that androgens may prevent preantral follicle growth and atresia [16][17][18][19][20]. Similarly, it has recently been shown that androgen receptor mRNA and androgen levels in follicular fluid correlate with FSH receptor mRNA expression in human granulosa cells from small antral follicles [21].…”
Section: Discussionmentioning
confidence: 99%
“…Androgens can augment FSH receptor expression in granulosa cells and are thought to promote follicular growth and estrogen biosynthesis by amplifying the effects of FSH in rhesus monkeys [15]. Studies on murine models of conditional granulosa cell and oocyte-specific deletion of the androgen receptor found positive correlations between androgen receptor and FSH receptor expression, suggesting that androgens may prevent preantral follicle growth and atresia [16][17][18][19][20]. Similarly, it has recently been shown that androgen receptor mRNA and androgen levels in follicular fluid correlate with FSH receptor mRNA expression in human granulosa cells from small antral follicles [21].…”
Section: Discussionmentioning
confidence: 99%
“…As we show that preovulatory androgens can promote follicle development and increase ovulation rates, whereas androgen excess is well established as one of the major causes of PCOS, we propose that there exists a critical balance between the essentiality of androgens in normal follicular development and the detrimental effects of androgens in the setting of androgen excess. In fact, the concept that androgens can promote follicle development is supported by the reported positive effects of androgen treatment in animals (7) as well as in patients with diminished ovarian reserve (22,23,50), in whom androgen priming is now being used in clinical settings to enhance ovulation (51,52).…”
Section: Nonspecific) (D-f)mentioning
confidence: 99%
“…A deficit of DHEA/T conversion has been identified in a subset of impaired ovarian reserve patients [34,35].…”
Section: How Fmr1 Mutations Influence Different Phenotypesmentioning
confidence: 99%